Stakeholders and procedures in the development of national training standards - a European comparative study - Philipp Ulmer; Marthe Geiben; Isabelle Le Mouillour; Anita Milolaza (Bundesinstitut für Berufsbildung (BIBB), 2021)
The design of vocational qualification standards is one of the key topics in current discussions and initiatives within reform processes of vocational education and training systems in Europe and worldwide. The BIBB research project addressed this issue and compared four countries with a dual training model - Germany, Austria, Switzerland, and Denmark - and two countries with a predominantly school-based training system - Portugal and Slovakia. This publication presents and discusses the procedures for developing qualification standards in the six countries and the underlying governance structures as well as an analysis of the interaction patterns of the main actors in the dual countries. It ends with impulses for international VET cooperation, thus addressing VET policy-makers and stakeholders.
urn:nbn:de:0035-0947-3
Keywords: 370